Gingival health status of patients treated with full veneer crown and contra lateral natural tooth : A comparative study - Mst Ummay Salma; Mohammad Arifur Rahman; Fatema Jannath; Sahara Akter; Md Amzad Hossain (Update Dental College, 2022)
Aim: The aim of this study was to compare the gingival health of patients treated with full veneer crown (FVC) restoration with the contralateral natural tooth of that patients in different stages of treatment. Materials and methods: This study compared the gingival health status of 30 endodontically treated posterior teeth with FVC and 30 contralateral natural teeth of 19 patients in terms of gingival index, and plaque index. These patients have been examined from July 2017 to June 2019 in the Dept. of Prosthodontics, Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital. The gingival health was assessed with gingival index and plaque index by Leo H in different stages of treatment, also compared with the contralateral natural teeth. Collected data were analyzed using SPSS software (version 22) according to the study objectives. Results: Tooth with FVC restoration found high gingival index and plaque index compared to a contralateral natural tooth in different stages of treatment. The mean differences of the gingival index were not significant at baseline, 4th month visits, but it was significant, and highly significant at 8th month, 12th month follow-up visits respectively. The mean differences in plaque index were found significant in all visits except 12th month visit. The gingival index and plaque index increased from baseline to 4th, 8th,12th month visits gradually both in abutments and contralateral natural teeth. Conclusion: If the FVC is fabricated with maintaining proper anatomical contour, equigingival margin with proper marginal adaptation, despite maintaining oral hygiene as well as the general health of patients there is a chance of development of adverse effects on gingival health in comparison to the contralateral natural tooth. Update Dent. Coll. j: 2022; 12 (1): 17-21